Validation of power measurement techniques in dynamic lower body resistance exercises - Cormie, P.; McBride, J. M.; McCaulley, G. O. (Journal of Applied Biomechanics, 2007)
The objective of this study was to investigate the validity of power measurement techniques utilizing various kinematic and kinetic devices during the jump squat (JS), squat (S) and power clean (PC). Ten Division I male athletes were assessed for power output across various intensities: 0, 12, 27, 42, 56, 71, and 85% of one repetition maximum strength (1RM) in the JS and S and 30, 40, 50, 60, 70, 80, and 90% of 1RM in the PC. During the execution of each lift, six different data collection systems were utilized; (1) one linear position transducer (1-LPT); (2) one linear position transducer with the system mass representing the force (1-LPT+MASS); (3) two linear position transducers (2-LPT); (4) the force plate (FP); (5) one linear position transducer and a force plate (1-LPT+FP); (6) two linear position transducers and a force place (2-LPT+FP). Kinetic and kinematic variables calculated using the six methodologies were compared. Vertical power, force, and velocity differed significantly between 2-LPT+FP and 1-LPT, 1-LPT+MASS, 2-LPT, and FP methodologies across various intensities throughout the JS, S, and PC. These differences affected the load-power relationship and resulted in the transfer of the optimal load to a number of different intensities. This examination clearly indicates that data collection and analysis procedures influence the power output calculated as well as the load-power relationship of dynamic lower body movements.